NEW WAY OF CONTROLLING Oryctes monoceros (COLEOPTERA, DYNASTIDAE), A COCONUT PEST IN GHANA - S.K. Dery; René Philippe (International Coconut Community Journal, 2004)
Oryctes monoceros is one of the most dangerous pests in young coconut and oil palm plantings throughout West Africa. This species is controlled using different methods that can be applied in combination as part of IPM. The first naturally involves eliminating all larva sites, consisting of dead or felled coconut or oil palm stems. Rapidly covering felled stems with a cover crop can keep the populations of this pest down to a very low level. When adults attack, frequent monitoring of young plantings is recommended, as is the removal of adults from their galleries using a metal mini-harpoon. Chemical control with Lambda-Cyhalothrin reduces damage to seedlings, particularly as that product has good repellent properties. It remains effective for around a month. Physical control has been developed, using old fishing nets rolled into balls and inserted in the axils of young fronds. This method is highly effective, cheaper than other types of control, does not pollute and is not toxic for handlers. Adults trapped by the rolled up fishing nets, which eventually die, attract other adults that are trapped in turn, thereby increasing the efficiency of the method.